Evaluation of Financial Liberalization : A General Equilibrium Model with Constrained Occupation Choice - Gine, Xavier; Townsend, Robert M. (World Bank, Washington, DC, 2014)
The objective of this paper is to assess both the aggregate growth effects and the distributional consequences of financial liberalization as observed in Thailand from 1976 to 1996. A general equilibrium occupational choice model with two sectors, one without intermediation, and the other with borrowing and lending, is taken to Thai data. Key parameters of the production technology and the distribution of entrepreneurial talent are estimated by maximizing the likelihood of transition into business given initial wealth as observed in two distinct datasets. Other parameters of the model are calibrated to try to match the two decades of growth as well as observed changes in inequality, labor share, savings, and the number of entrepreneurs. Without an expansion in the size of the intermediated sector, Thailand would have evolved very differently, namely, with a drastically lower growth rate, high residual subsistence sector, non-increasing wages, but lower inequality. The financial liberalization brings welfare gains and losses to different subsets of the population. Primary winners are talented would-be entrepreneurs who lack credit and cannot otherwise go into business (or invest little capital). Mean gains for these winners range from 17 to 34 percent of observed overall average household income. But liberalization also induces greater demand by entrepreneurs for workers resulting in increases in the wage and lower profits of relatively rich entrepreneurs of the same order of magnitude as the observed overall average income of firm owners. Foreign capital has no significant impact on growth or the distribution of observed income.